MANAGEMEN DALAM PROSES PEMBELAJARAN Di SMTKN DAN SMPTK SE-PAPUA BARAT - Habel S.J. Rieuwpassa (KOLONI, 2022)
Diaspora SMTKN, Pelita Sembab SMTKN, Kaimana SMTKN have been established since 2006 which were originally under the auspices of the Sorong Papua Diaspora Foundation. Then there are 6 SMPTK in West Papua which play a role in the world of education. In terms of community interest in this school, the author assumes that there is a negative stigma, this can be seen from the number of new student admissions from year to year which does not meet the maximum target, for example for the 2020-2021 Academic Year the acceptance of new students at Sembab Manokwari High School has a total of 20 new students. SMTKN Kaimana 20 Students SMTKN Diaspora 35 students, the same thing also happened to SMPTK in West Papua. The learning process at the SMATKN and SMPTK Religious Schools in West Papua Province needs special attention in order to improve the quality of the learning process so that the resulting output has a positive impact on the community and also has a positive impact on community demand. Special attention is needed to make improvements to the management of the learning process which involves teaching staff, educational staff and stakeholder involvement through the school committee. The purpose of this paper is to examine and analyze the application of management functions in the learning process so that it can improve the quality of education at SMKN and SMPTK throughout West Papua Province. This research was conducted using a qualitative approach. Keywords: Implementation of Management, Learning Process, SMTKN and SMPTK